A Snapshot of OpenMP Projects on GitHub - Quevedo, Cristian Carvalho; Oliveira Jr., Marcos Antonio de; Du Bois, André Rauber; Cavalheiro, Gerson Geraldo H. (Anais do Simpósio Brasileiro de Linguagens de Programação (SBLP), 2024)
This paper presents a mapping of the use of the OpenMP API in open-source projects hosted on GitHub. A case study collected data on using OpenMP directives following a mining process in repositories developed in C and C++ with OpenMP. The study analyzed the use of OpenMP resources to support critical sections and exploit data parallelism. The analysis reveals usage patterns of such resources that limit the parallelization potential obtainable with this programming tool. The results contribute to understanding how the community uses this tool and provide insights for developing better practices and tools to support the use of OpenMP and improve the teaching of parallel processing. All software artifacts developed for this study are available to foster reproducibility and further research.